Food Addiction Does Not Explain Weight Gain in Smoking Cessation - Amer Nordin, Amer Siddiq; Adamson, Simon Justin; Sellman, John Douglas (Cambridge University Press, 2018)
Introduction: Weight gain during smoking cessation is a major concern. The relationship between smoking and weight is complex and not well understood. There is interest in substitution of nicotine with food. Aims: This study investigates whether the development of food addiction explains weight gain following a quit smoking attempt. Methods: This study was a subset of a larger study investigating smoking cessation in New Zealand. Participants were assessed on five visits over a 1-year period. Using validated instruments, measurements for smoking, weight, food intake, craving and food addiction were taken. Results: Among the 256 participants, 54.7% attended at least one follow-up. Food addiction prevalence at baseline was 0.8%. 14.5% were quit at early follow-up and 14.8% at late follow-up. Weight gain was found in abstainers compared to those still smoking. No increase in food addiction was detected. Conclusion: The development of food addiction does not play a prominent role in post quit weight gain. Further research is needed to elucidate the underlying weight gain mechanisms.